The Hippocampal Neuroproteome with Aging and Cognitive Decline: Past Progress and Future Directions - VanGuilder, Heather; Freeman, Willard (Frontiers in Aging Neuroscience, 2011)
The biological basis of brain aging and non-neurodegenerative cognitive decline is unknown and for a number of decades steady progress on understanding brain aging has been made using traditional anatomic, immunohistochemical, and molecular technologies. With the development and maturation of proteomic technologies the application of these approaches to neuroproteomic studies of brain aging and cognitive decline is becoming more widespread. This review examines the progress in the field and challenges to be addressed. Accumulating neuroproteomic data demonstrate that brain aging involves dysregulation of metabolism, increased oxidative stress, altered protein modification and trafficking, and decreased synaptic function. Additionally, growing evidence suggests that cognitive decline does not represent a ‘more aged’ phenotype, but rather is associated with specific neuroproteomic changes that occur in addition age-related alterations. Understanding if and how age-related changes to the neuroproteome contribute to cognitive decline and elucidating the pathways and processes that lead to cognitive decline are critical objectives that remain to be achieved. Broad collaborative efforts and establishment of standard models and approaches are required to maximize the benefit of comprehensive neuroproteomic analyses to the aging research field.